Spiritual Emotional Freedom Technique (SEFT) as an Effort to Improve Mood Swing Premenstruation Syndrome - Indah Lestari (STIKes Patria Husada Blitar, 2023)
Towards or during the menstrual cycle there are changes in the balance of various hormones such as endorphins, serotonin, and other hormones that determine mood. Mood swings, commonly known as premenstrual syndrome, fluctuate involving alternating feelings of happiness, sadness, anger, and depression, which are often known as Mood Swings. This condition can be minimized with non-pharmacological therapy, one of which is SEFT (Spiritual Emotional Freedom Technique). The purpose of this study was to prove the effect of SEFT (Spiritual Emotional Freedom Technique) therapy in improving the mood of Premenstrual Swing Syndrome at Darussalam Islamic Boarding School. The research design was a pre-experimental one-group pretest-posttest approach. The research population was all female students who experienced premenstrual syndrome Mood Swings at Darussalam Islamic Boarding School with a total of 232 respondents. A sample of 186 respondents, was selected by random sampling technique. The instruments in the study were standard SEFT therapy procedures and the FDMS (Four Dimension Mood Scale)